T Cells in the Female Reproductive Tract Can Both Block and Facilitate HIV Transmission - Miller, Christopher J. (Curr Immunol Rev, 2019)
Because HIV is sexually transmitted, there is considerable interest in defining the nature of anti-HIV immunity in the female reproductive tract (FRT) and in developing ways to elicit antiviral immunity in the FRT through vaccination. Although it is assumed that the mucosal immune system of the FRT is of central importance for protection against sexually transmitted diseases, including HIV, this arm of the immune system has only recently been studied. Here we provide a brief review of the role of T cells in the FRT in blocking and facilitating HIV transmission.